Segmented dike intrusion linked to multi-level magma storage during and before the 2025 eruption at Erta Ale (East Africa) - La Rosa, Alessandro; Pagli, Carolina; Keir, Derek; Ayele, Atalay; Wang, Hua; Rivalta, Eleonora; Lewi, Elias (Frontiers in Earth Science, 2025)
IntroductionDike intrusions can assist continental rifting and plate divergence. However, our understanding of the magma dynamics during diking and the architecture of the magma storage that feeds dikes are still limited by temporally and spatially sparse dataset.MethodIn this study we used multiple evidence from InSAR, optical data, pixel offset tracking and seismicity to reconstruct the temporal evolution of the intrusion and the magma storage that fed the dike at the Erta Ale volcanic system (Afar Rift, East Africa), before and during the recent volcanic activity of July-August 2025.ResultsDuring 25 days, a dike propagated southward for 36 km, intruding a total of ∼0.3 km3 of mafic magma. InSAR modelling showed the dike intrusion was fed by multiple magma bodies, including a dike-shaped magmatic source and two shallow (∼1 km) magmatic sills. InSAR time-series of the pre-diking period also revealed a deeper (∼7 km) magmatic source that could have partially supplied the intrusion.DiscussionThe event, while much larger in volume, shows similarities to previous dike intrusions at Erta Ale, implying the presence of a long-lived multi-level magma storage system within the Erta Ale volcanic system.